Assessment of levels of Vitamin D and Leptin in comparison of BMI among medical students - Sivakumar J.; Ursula Sampson; Kumar J. (International Journal of Medical Research and Review, 2020)
Introduction: Vitamin D is one of fat-soluble vitamin that plays an important role in the absorption of calcium and phosphate. Deficiency of Vitamin D is unrecognized in many parts of the world. Leptin is a hormone which is derived from adipose tissue. Studies have shown that vitamin D has a negative and powerful control on leptin secretion by vitamin D by acting on the adipose tissue.Aim and Objectives: The study was done to study the relationship between Vitamin D and Leptin based on Body mass index among the medical students.Materials and methods: Vitamin D Leptin and Body mass index were the parameters measured in the study group. Individuals with an age group of 19-23 years of both sexes were included in the study. Individuals above the age of 23 years, those with renal and liver disorders, individuals with hormonal disorders, individuals on vitamin D supplementation were excluded in the study. Vitamin D was measured by Enzyme-Linked Immunosorbent Assay (ELISA) method. Leptin was measured by Enzyme-Linked Immunosorbent Assay (ELISA) method. BMI is calculated by the formula weight in kilograms divided by height in metre square.Results: The results have shown that there is a decrease in vitamin D levels with increasing BMI. (pvalue≤0.001). furthermore, there is an increase in leptin levels with an increase in BMI. (pvalue≤0.001).Conclusion: The study has put forth a suggestion that leptin and vitamin D has a causal relationship between them based on Body Mass index. Adequate vitamin D levels will maximize the effect of maintaining normal leptin levels as high levels of leptin could contribute to obesity-related disorders.